Socio-demographic, agricultural, and personal protective factors in relation to health literacy among farmers from all regions of Thailand - Sapbamrer, Ratana; Sittitoon, Nalin; Thongtip, Sakesun; Chaipin, Eakasit; Sutalangka, Chatchada; La-up, Aroon; Thirarattanasunthon, Phiman; Thammachai, Ajchamon; Suwannakul, Boonsita; Sangkarit, Noppharath; Kitro, Amornphat; Panumasvivat, Jinjuta; et al. (Frontiers in Public Health, 2024)
Introduction: Farmers are vulnerable to adverse health effects from pesticide exposure due to their health literacy (HL). Therefore, this study aims to investigate HL among farmers in four main regions of Thailand, investigating socio-demographics, agricultural, and personal protective factors to their HL. Methods: This cross-sectional design study was conducted on 4,035 farmers from January to July 2023. The European Health Literacy Survey Questionnaire-47 items were used to measure HL. Results: Thai farmers had a mean HL score of 34.7+ 8.7, and the farmers in the North region of Thailand had the highest frequency of limited HL (75.8%). Socio-demographic factors that were associated with HL included gender, region of living, marital status, education level, co-morbidity, and number of family members. Agricultural factors associated with HL included planting status, working hours on farm, spraying pesticides, harvesting crops, pesticide use of >1 type, access information from government officers, access information from posters/brochures, information from online multimedia, and access information from neighbors. Personal protective factors that were associated with HL included wearing a hat, goggles, a rubber apron, and a long-sleeved shirt. Discussion: Our study recommends that strategies and interventions to enhance the HL of farmers should be focused on the target populations which include men, widows or divorced, those with low levels of education, those who have co-morbidities, and those who applied pesticides of more than 1 type and improper personal protective equipment (PPE) use. The primary emphasis needs to be on the North region of Thailand, making that the target area to improve health equity in Thailand. These efforts would enhance the HL of farmers and sustainably improve pesticide safety behavior. Additionally, there's an urgent need for supportive measures aimed at altering on-farm practices and promoting education on alternative pest management strategies, particularly non-chemical crop protection, to ensure sustainable agriculture.